2013
DOI: 10.3126/jmcjms.v1i1.7884
|View full text |Cite
|
Sign up to set email alerts
|

Research article Evaluation of Genotype MTBDRplus Assay for identifying Multidrug Resistant Mycobacterium tuberculosis isolates in Nepal

Abstract: Background and Objectives: Multidrug-resistant (MDR) Mycobacterium tuberculosis strains are serious threats to the control of tuberculosis and comprise an increasing public health problem. Rapid detection of such strains is quite critical in timely management of such issues. The study was performed with an objective to compare Genotype MTBDRplus reverse hybridization probe assay (Hain Lifescince, GmBH, Nehern, Germany) with culture based proportion method for rapidly identifying MDR-TB strains from suspected m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 11 publications
3
1
4
Order By: Relevance
“…S531L missense mutation that led amino acid substitutions of serine to threonine was most common in rpoB gene accounting for 50% (17/34) of all RIF resistant isolates. Similar result was found in South Vietnam [ 20 ] but it was found to be less frequent than in Thailand (63.6%) [ 21 ] and India (72%) [ 22 ] and more frequent than in a study from Nepal (37.14%) [ 16 ]. Amino acid substitution of aspartate to valine at 516 codon of rpoB gene was observed in 23.5% (8/34) of the RIF resistant strains studied.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…S531L missense mutation that led amino acid substitutions of serine to threonine was most common in rpoB gene accounting for 50% (17/34) of all RIF resistant isolates. Similar result was found in South Vietnam [ 20 ] but it was found to be less frequent than in Thailand (63.6%) [ 21 ] and India (72%) [ 22 ] and more frequent than in a study from Nepal (37.14%) [ 16 ]. Amino acid substitution of aspartate to valine at 516 codon of rpoB gene was observed in 23.5% (8/34) of the RIF resistant strains studied.…”
Section: Discussionsupporting
confidence: 77%
“…Amino acid substitution of aspartate to valine at 516 codon of rpoB gene was observed in 23.5% (8/34) of the RIF resistant strains studied. This frequency was higher than recent studies reported from Nepal (5.71%) [ 16 ] and India (3.03%) [ 22 ]. Although various frequencies of mutation (2.8%–40%) are observed geographically in different regions of the world at codon 526 of rpoB gene substituting amino acid histidine [ 16 , 19 , 23 , 24 ], no mutation was observed in this gene region in this study.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In the present study, the predominant mutation for RIF resistance was found to be in rpoBS531L (71%), which was in agreement with the finding by Yadav et al (72%) [ 5 ]. Lower rates of S531L missense mutation in rpoB gene in comparison to our study were reported by Sharma et al (50%) [ 2 ] and Dahal et al (37.1%) [ 8 ]. In our study, the substitution of aspartate by valine at codon 516 of rpoB gene was found in 4.8% of the RIF resistant isolates which was similar to the findings of the studies in Nepal (5.7%) [ 8 ] and India (3.%) [ 5 ].…”
Section: Discussioncontrasting
confidence: 60%
“…Lower rates of S531L missense mutation in rpoB gene in comparison to our study were reported by Sharma et al (50%) [ 2 ] and Dahal et al (37.1%) [ 8 ]. In our study, the substitution of aspartate by valine at codon 516 of rpoB gene was found in 4.8% of the RIF resistant isolates which was similar to the findings of the studies in Nepal (5.7%) [ 8 ] and India (3.%) [ 5 ]. In the present study, mutation in rpoBH526Y site was observed in 3.2% of the RIF resistant isolates.…”
Section: Discussioncontrasting
confidence: 60%